Homeowner's tax breaks - Gerald J. Robinson, (John Wiley & Sons, Inc., 2004)
Gerald J. Robinson, Esq., tax counsel to the New York City law firm of Carb, Luria, Cook & Kufeld, is a member of the New York and Maryland bars. He received his BA degree from Cornell University, an LLB from the University of Maryland, and an LLM in Taxation from New York University. Prior to entering private practice, he served in the Office of Chief Counsel, Internal Revenue Service. He is the author of the treatise, Federal Income Taxation of Real Estate, now in its sixth edition, and wrote the monthly newsletter, â€œReal Estate Tax Ideas,â€ both published by Warren, Gorham & Lamont. He is also a frequent lecturer and contributor to various professional journals.